Ολισθηρότητα και μακρουφή των οδοστρωμάτων κυκλοφορίας - Χριστοδούλου, Αντρέας (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικης, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
The surface characteristics of the road which are directly related to the functionality of the road are those associated with the geometric profile in the vertical plane. This research examines the adequacy of the road surface and the important role played by the sliding resistance and macro-texture of the road on the functionality of a street or an avenue in general. The purpose of this thesis is to analyze further these two factors (macro-texture and sliding) as to how to measure them, their importance to the road surface and the correlation with other factors such as traffic volume and its frequency as well as the pedestrian traffic around the road. This correlation will be done through a risk evaluation methodology. The risk assessment will be presented through a quantitative yield of jeopardy which has as main factors the risk and its consequences. In this thesis it will also be presented how the traffic surface of the road is calculated. The main data that will be used for this calculation are driver's visibility length, the vehicle's stopping distance, the vehicle's impact speed and the risk index of the road surface which arises from slip resistance and macrotexture values of the road. In addition, there is a presentation of the measurements taken on routes within the network of Cyprus University of technology (CUT) relative to the slipperiness and macrotexture of the road. Applications will also be made for this network with examples of points within the network showing the degree of risk.
Keywords: Road; Sliding Resistance; Οδόστρωμα; Αντίσταση και Ολίσθηση